An Exploration of the Effects of Tibetan Yoga on Patients' Psychological Well-Being and Experience of Lymphoma: An Experimental Embedded Mixed Methods Study. (January 2018) - Leal, Isabel; Engebretson, Joan; Cohen, Lorenzo; Fernandez-Esquer, Maria Eugenia; Lopez, Gabriel; Wangyal, Tenzin; Chaoul, Alejandro
As an emergent care model combining conventional with complementary therapies, integrative interventions challenge evaluation, necessitating approaches capable of capturing complex, multilevel interactions. This article evaluates the effects of a Tibetan yoga intervention on lymphoma patients' quality of life and cancer experience. Our methodological aims were to explore differences in therapeutic effect between treatment and control group using qualitative data, and explain equivocal findings between data sets. Use of both data transformation techniques—qualitizing and quantitizing—within an experimental embedded design comparing and integrating data between data sets and treatment groups allowed us to develop this innovative evaluative approach. Findings clarify convergence and divergence between data sets, explore participants' complex cancer experience, and capture dimensions and intervention effects inaccessible through either method alone.